Copyright and information privacy : conflicting rights in balance - Giovanella, Federica (Edward Elgar Publishing, 2017)
Federica Giovanella examines the on-going conflict between copyright and informational privacy rights within the judicial system in this timely and intriguing book. Adopting a comparative approach focusing on the United States, Canada and Italy, Dr Giovanella skilfully explores the strategies through which judges solve conflicts between Internet users' data protection and copyright holders' enforceable rights. Using research centred on a selection of lawsuits in which copyright holders attempted to enforce their rights against Internet users suspected of illegal file-sharing, this book analyses the cases and regulatory frameworks concerning both privacy and copyright. Copyright and Information Privacy demonstrates that these decisions were ultimately the by-products of different policy conceptions of the two conflicting rights.-